2011
DOI: 10.1177/0891988711422524
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Related Cognitive Dysfunction in Dementia Caregivers

Abstract: SUMMARY In a cross-sectional study, 31 dementia caregivers were compared to a group of 25 non-caregiving controls to evaluate whether the stress of being the primary caregiver of a person with dementia produces cognitive dysfunction. Cognitive differences were examined to evaluate the relationships between cognitive function and stress-related physiological and psychological measures to contribute information regarding its potential mechanism. The cognitive assessments were two measures of attention-executive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
5
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 56 publications
(94 reference statements)
5
85
5
3
Order By: Relevance
“…Oken et al (2011) found that, when compared to non-caregiving controls, dementia caregivers performed significantly worse on cognitive tasks and mediation analysis revealed that impaired sleep was the sole mediator of impaired cognitive performance.…”
Section: Meditation-based Interventions For Dementia Caregiversmentioning
confidence: 93%
“…Oken et al (2011) found that, when compared to non-caregiving controls, dementia caregivers performed significantly worse on cognitive tasks and mediation analysis revealed that impaired sleep was the sole mediator of impaired cognitive performance.…”
Section: Meditation-based Interventions For Dementia Caregiversmentioning
confidence: 93%
“…Results and complete methods for these trials are reported elsewhere. [27][28][29][30] Methods relevant to this analysis are included here. The first trial (referred to as MB III by the original lab for Mind-Body trial 3) was a 3-arm randomized controlled trial of mindfulness meditation in healthy adults, aged 50 to 85, who are caregivers for people with dementia.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, researchers have considered whether the stresses associated with providing dementia care might also impact on CG's own cognitive functioning (Fonareva and Oken, 2014). Several studies have reported that CGs have poorer performance than NCGs on cognitive domains such as processing speed (de Vugt et al, 2006;Oken et al, 2011;Vitaliano et al, 2009), working memory (e.g., Mackenzie et al, 2009), and delayed recall (e.g., de Vugt et al, 2006;Mackenzie et al, 2009). Furthermore, a population-based study on more than a thousand married couples over the age of 65 reported that spouses of people with dementia were 1.62 times more likely to develop incident dementia than individuals whose spouses were dementia free, even after accounting for risk factors such as age, sex, education, socio-economic status and Apolipoprotein E (APOE) genotype (Norton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%